2010
DOI: 10.1186/1532-429x-12-13
|View full text |Cite
|
Sign up to set email alerts
|

How do hypertrophic cardiomyopathy mutations affect myocardial function in carriers with normal wall thickness? Assessment with cardiovascular magnetic resonance

Abstract: BackgroundClinical data on myocardial function in HCM mutation carriers (carriers) is sparse but suggests that subtle functional abnormalities can be measured with tissue Doppler imaging before the development of overt hypertrophy. We aimed to confirm the presence of functional abnormalities using cardiovascular magnetic resonance (CMR), and to investigate if sensitive functional assessment could be employed to identify carriers.Results28 carriers and 28 controls were studied. Global left atrial (LA) and left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 30 publications
4
38
0
3
Order By: Relevance
“…The increased myofilament Ca 2+ sensitivity and high sarcomere stiffness in the presence of ADP is in line with our previous study, where we showed that the complex interactions of Ca 2+ and ADP increased myofilament Ca 2+ sensitivity and stiffness in membrane-permeabilized rat cardiomyocytes, limited restoration of diastolic length in intact rat cardiomyocytes, and diminished ventricular compliance in whole rat hearts (17). Altogether, these myofilament changes have the potential to delay the onset of ventricular relaxation and limit proper filling, which are seen in patients (54,55) and animal models (51, 52) of HCM, and human IDCM (4).…”
Section: Discussionsupporting
confidence: 75%
“…The increased myofilament Ca 2+ sensitivity and high sarcomere stiffness in the presence of ADP is in line with our previous study, where we showed that the complex interactions of Ca 2+ and ADP increased myofilament Ca 2+ sensitivity and stiffness in membrane-permeabilized rat cardiomyocytes, limited restoration of diastolic length in intact rat cardiomyocytes, and diminished ventricular compliance in whole rat hearts (17). Altogether, these myofilament changes have the potential to delay the onset of ventricular relaxation and limit proper filling, which are seen in patients (54,55) and animal models (51, 52) of HCM, and human IDCM (4).…”
Section: Discussionsupporting
confidence: 75%
“…Elevated EF 21,39,40 and hypercontractility 41 have been previously documented, but diastolic 42 and systolic dysfunction 43 have also been seen, although the latter may have been attributable to myocardial scar, 43 whereas our carriers were entirely free of scar. Elongation of the AMVL was also confirmed.…”
Section: Discussionmentioning
confidence: 90%
“…Puntman et al found that in hypertensive patients LV wall stress was increased whereas patients with HCM were characterized by reduced total longitudinal strain [10]. The combination of anatomical and functional parameters have been shown to increase the diagnostic accuracy to detect HCM causing mutation carriers from healthy controls [29]. Also, late gadolinium enhancement (LGE) imaging has been suggested to increase diagnostic accuracy in patients with mild to moderate hypertrophy.…”
Section: Discussionmentioning
confidence: 98%